Forest and Land Rehabilitation Planning Based on Land Capacity of The Lake Tondano Catchment Area - Hengki Djemie Walangitan (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2014)
This study aims to analyze and develop alternative forest and land rehabilitation based on land capability in catchment area Tondano lake. Inhibiting factors used in the analysis is the ability of land slope, drainage and infiltration rate. The results of the analysis obtained 42 units of land. Approximately 85 % belong to the class I - V and 15 % belong to the class VI-VIII. Furthermore, the proposed three models of forest and land rehabilitation as follows: (1) Sub East catchment area, proposed pattern-based agroforestry clove plants in cultivation area, (2) Sub South catchment area, proposed pattern of farm crops is designed in agroforestry systems so that the health of soil, especially soil organic matter content can be maintained to support sustainable agriculture, (3) Sub West catchment area, proposed pattern integrated farming cattle crops (maize + grass strip + terrace ridges). While in the forest area developed multi purposes forest on all catchment areas.